Strategi Pemberdayaan Ekonomi Jemaat Sebagai Aksi Pastoral - Mangintiu, Meylan; Nyortetma, Devence; Salindeho, Sri Apria; Bambung, Charolin; Papehasen, Christian; Amping, Eunike; Inaku, Rahel; Manggiwu, Sindy; Biala, Trisakti; Binilang, Yanly; Hender, Solistiyo; Piandatu, Natasya (PT. Giat Konseling Nusantara, 2024)
By exploring various plans that are prepared as an integral part of the church's pastoral action, through approaches that can improve the economic welfare of the congregation and practical spiritual support from the church. In several sections it can be seen how the church plays an active role in encouraging economic independence which strengthens community life and improves the quality of life of the congregation, and we need to know that the factor that drives congregational independence is the pastoral role in the community service program that has been implemented, so it is necessary for us to understand how step by step the pastoral service strategy is implemented at GMIST Wori Congregation in the